NIR-responsive nanomaterials and their applications; upconversion nanoparticles and carbon dots: a perspective - Chien, Yi-Hsin (2019)
Near‐infrared (NIR) light responsive materials have received much attention for diverse applications due to their excellent optical properties. This type of material exhibits upconverted luminescence, a non‐linear optical process in which two or more low energy photons, usually from NIR light irradiation are transformed to high energy photons emission through energy transfer upconversion, excited state absorption, photon avalanche or multiphoton absorption. The NIR range of excitation source is favorable for biological imaging and cancer theranostic applications due to their high penetration depth, low autofluorescence, minimal light scattering, reduced photodamage, and negligible phototoxicity. Having these properties, NIR responsive materials such as upconversion nanoparticles (UCNPs) and carbon dots (CDs) which perform upconversion luminescence are actively exploited in a wide variety of applications such as display and sensory technology. While CDs are well known for their versatility in using different chemicals and green precursors to achieve tunable optical properties, UCNPs also have the advantage that a continuous‐wave NIR laser can be used as the excitation source. This article reviews the properties of these two materials in the aspects of luminescence mechanisms and their recent developments in cancer theranostics, display technology, biosensing and metal ions sensing applications. © 2018 Society of Chemical Industry